A Roadmap for successful IoT implementation : empirical evidence from the energy industry - Hafeez, Shahid; Juszczyk, Oskar; Takala, Josu (IACIS International Association for Computer Information Systems, 2021)
The Internet of Things has become a spotlight in contemporary literature in the domain of industry 4.0 and emerging technologies. Majority of research studies focuses on technicalities and theoretical implications of implementing IoT in the energy sector. However, in practice, organisations face a combination of technical and non-technical challenges. There is a clear need for the studies to empirically evaluate IoT use cases, challenges, and a roadmap for successfully implementing emerging technologies. To fulfil the research gap and provide insights for practitioners, we conducted seven semi-structured interviews with professionals working in Finland’s energy sector. Based on results retrieved through content analysis of transcribed interviews, we developed a roadmap with managerial implications for successfully implementing IoT and other emerging technologies. Furthermore, study results present practical insights on IoT applications, benefits, and major IoT utilisation challenges in the Finnish energy sector industrial ecosystem. In the end, conclusion and future research directions are discussed.
Keywords: industry 4.0; innovation management; product development; manufacturing; implementation roadmap; Internet of things; fi=Tuotantotalous|en=Industrial Management|